MODERATOR EFFECT OF MALADAPTIVES SCHEMES IN THE RELATIONSHIP BETWEEN SPIRITUALITY AND VIOLENCE TENDENCY - EKŞİ, HALİL; OKAN, NESRULLAH (ILAHIYAT BILIMLERI ARASTIRMA VAKFI, 2021)
The young mass, which is the guarantee of the future of nations and societies, is undoubtedly very important for every society. Because if one wants to have a prediction about the future of a society, it will be sufficient to look at how future generations are educated and what kind of behavior patterns they have. Especially in recent times, youth's attitudes towards violence have an important place in Turkish society. Therefore, the tendency of young people towards violence and violence is one of the most important issues that started to be discussed in the society. So much so that it is normal to encounter situations related to violence in all segments and levels of society. Especially in youth individuals, this phenomenon of violence manifests itself more clearly. It is an important issue to determine the underlying factors of violence, which is more common among young people, especially in the community. It is known that important studies have been carried out in the context of state policies and researchers in order to reveal the reasons for this important issue. In this study, the moderator (regulatory) role of early maladaptive schemas in the relationship between spirituality and violent tendencies was investigated. The sample of the study consists of 446 individuals studying at 5 different high schools in the Anatolian side of Istanbul. The data of the study were obtained with the Attitude towards Violence Scale, Spiritual Orientation Scale and Young Schema Scale Short Form-3. The analysis of the data was carried out with SPSS 22.0 and AMOS 20.0 programs. Moderator (regulatory) variable analysis was applied to the research data, and according to the analysis results, it was found that the early period maladaptive schemes of addiction (addiction / inadequacy schemes and intimacy / undeveloped self) and punishment schemes had a moderator (regulator) role in the relationship between spirituality and violence tendency.
Keywords: Psychology of Religion; Spiritual Psychology; Spirituality; violence; early maladaptive schemes; moderator effect; MENTAL-HEALTH; RELIGION; WOMEN